The dark is rising [compact disc, unabridged] - Cooper, Susan, 1935- (Cooper, Susan, 1935- Dark is rising sequence (Listening Library), 2007)
On his eleventh birthday Will Stanton discovers that he is the last of the Old Ones, destined to seek the six magical Signs that will enable the Old Ones to triumph over the evil forces of Dark.